RATING DAN PERAN AKTIF KONSUMEN MEDIA DALAM POLITIK KONGLOMERASI - Hanna Auliya; Miftakhul Rohman (Universitas Nahdlatul Ulama Blitar, 2021)
Talking about the media in Indonesia commonly related to politics and personal interests which known as media conglomerates. The media should have balanced principle in every delivered information, but in fact the media now has to reverse direction to follow the interests of media owners. In this article, the author discusses ratings and an active role in the media with media conglomerates, which in fact both are interconnected. This article found that rating and active role of consumers in the media determine the content of an event. Conglomerates in Indonesia also have a tendency to become a media commercialization.